DETECTION, TRANSMISSION, AND EXPRESSION cDNA GROWTH HORMONE GENE (PhGH) OF STRIPPED CATFISH IN F-1 TRANSGENIC AFRICAN CATFISH - Huria Marnis; Bambang Iswanto; Rommy Suprapto; Imron Imron; Raden Roro Sri Pudji Sinarni Dewi (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2014)
In previous study, the fast growth transgenic founder of African catfish was produced harboring a growth hormone (GH) gene construct containing a stripped catfish growth hormone (PhGH) cDNA. This study was conducted to investigate transgene (PhGH) transmission and expression in F-1 transgenic African catfish. The transgenic founders (female) were crossed with non-transgenic (male) to produce heterozygous F-1 progeny. PhGH gene was detected in the embryo, larvae, and seed of the transgenic F-1 using PCR method. Expression levels of transgene in embryo and larvae were analyzed using real-time quantitative PCR (qPCR) method. The transgene was detected in embryo, larvae and seed of F-1 transgenic African catfish. Founder could transmit PhGH gene to transgenic F-1 lines in ranged 36% to 48%. Expression level of Phgh gene in embryo was higher than that of the larvae; whereas in the embryo was 1.5 x 105 - 5.2 x 105 copies or 0.49-9.82 fold, while in the larvae was 1.1 x 105 - 2.5 x 105copies or 0.19-5.80 fold.